Pneumonitis and multiple pneumonial infections under combined immune‐checkpoint inhibition - Kristine E. Mayer; Thomas Gan; Jochen Gaa; Tilo Biedermann; Christian Posch (JEADV Clinical Practice, 2023)
Abstract The introduction of immune checkpoint inhibitors and targeted therapies has revolutionized melanoma treatment. The downside are immune‐mediated adverse events which are frequent and require close patient management. We report a case of severe immune‐mediated hepatitis and pneumonitis under combined immune‐checkpoint inhibitor therapy requiring immunosuppressive therapy. Under immunosuppressive therapy, however, a series of opportunistic infections occurred. It can be challenging to distinguish the signs of immune‐mediated adverse events of checkpoint inhibitors and pathogen‐mediated inflammation due to overlaps in clinical and laboratory findings. This case has the goal to rise awareness for infectious complications during immunosuppressive therapy needed to address immune‐mediated adverse events of checkpoint inhibitors.